ANALISIS GERAK NOMOR LARI SPRINT 100 METER PUTRA CABANG OLAHRAGA ATLETIK (STUDI KASUS PADA USAIN BOLT DI KEJUARAAN INTERNATIONAL ASSOCIATION OF ATHLETICS FEDERATION BERLIN TAHUN 2009) - Nurhayati, Cici Diah Lutfi (Jurnal Kesehatan Olahraga, 2019)
One of favorite and popular prestigious athletics sports is sprint with 100 meters track distance. World record in sprint 100 meters is Usain Bolt has won the sprint contest ofInternational Association Athletics Federations (IAAF) Championships in Berlin 2009 and achived9,58 second is worldwide. The purpose of this study is to determine the speed and biomechanical movement of the sprint in the final 100 meters Usain Bolt at the International ASSOCIATION Of Athletics Federations (IAAF) Championship in Berlin 2009. This research method used quantitative descriptive analysis method with no test technique using observation. In this study the data sources was the video final of 100 meters men on the Usain Bolt at the International Association Of Athletics Federations (IAAF) Championship in Berlin 2009. Data analysis techniques by using observations method the assisfed analysis applications named kinovea. The results of this study is within 100 meters Usain Bolt distance of 9,58 second, with a time interval of 0,83 second, which produce the highest average speed of 12,35 m/s with the highest step of lenght of 2,77 meters with an angle of 125º reached at a distance of 80 meters and the average step length of 2,6 meters resulting in a total frequency step are 41 steps. Keywords: Motion Analysis, Speed, Footstep, Step Length, Frequency Step, Sprint 100 meters.